Analyzing the Influence of Bedrock Geometry on Ambient Vibration Using HVSR and Particle Dynamics - Fazah, Hanum; Rosandi, Yudi (Spektra: Jurnal Fisika dan Aplikasinya, 2025)
Ground vibration signals recorded by low-frequency multi-channel geophones provide information about the physical characteristics of a medium. Using the passive seismic method, vibrations are measured in three channels, i.e. horizontal and vertical directions. Since the characteristics of mediums, such as sediment thickness and soil hardness, are contained in low-amplitude ambient vibrations, further data selection is required to remove spikes in the signals induced by active sources. This work is necessary to reveal the characteristics that reflect the mediums’ physical condition from the signal. Conventionally, signal processing is based on the Horizontal-to-Vertical Signal Ratio (HVSR) calculation. The information obtained, such as sediment thickness and sub-surface shear velocity (Vs30), as well as the amplification factor and seismic vulnerability, are crucial for geotechnical applications. This data can be extracted from HVSR analysis. However, a complete understanding of the complex vibration signal shape related to the medium and local geological conditions is not fully understood. To gain a deeper understanding of the mechanism, numerical modeling is performed using a particle dynamics method. The vibration pattern of chosen particles on the surface was studied and its relation to the geometry of the fixed base region was investigated. The simulation results show systematic changes in signal form when processed with a similar HVSR method as a response to the shape of the fixed base.